Normothermic ex vivo lung perfusion using a developed solution followed by orthotopic left lung transplantation (experimental study) - I. V. Pashkov; S. V. Gautier; V. K. Bogdanov; D. O. Oleshkevich; D. M. Bondarenko; N. P. Mozheiko; N. S. Bunenkov; N. V. Grudinin (Вестник трансплантологии и искусственных органов, 2023)
The continued unavailability of adequate organs for transplantation to meet the existing demand has resulted in a major challenge in transplantology. This is especially felt in lung transplantation (LTx). LTx is the only effective method of treatment for patients with end-stage lung diseases. Normothermic ex vivo lung perfusion (EVLP) has been proposed to increase the number of donor organs suitable for transplant – EVLP has proven itself in a number of clinical trials. The ability to restore suboptimal donor lungs, previously considered unsuitable for transplantation, can improve organ functionality, and thus increase the number of lung transplants. However, widespread implementation of ex vivo perfusion is associated with high financial costs for consumables and perfusate.Objective: to test the developed solution on an ex vivo lung perfusion model, followed by orthotopic LT under experimental conditions.Materials and methods. The experiment included lung explantation stages, static hypothermic storage, EVLP and orthotopic left LTx. Perfusion was performed in a closed perfusion system. We used our own made human albumin-based perfusion solution as perfusate. Perfusion lasted for 2 hours, and evaluation was carried out every 30 minutes. In all cases, static hypothermic storage after perfusion lasted for 4 hours. The orthotopic single-lung transplantation procedure was performed using assisted circulation, supplemented by membrane oxygenation. Postoperative follow-up was 2 hours, after which the experimental animal was euthanized.Results. Respiratory index before lung explantation was 310 ± 40 mmHg. The PaO2/FiO2 ratio had positive growth dynamics throughout the entire EVLP procedure. Oxygenation index was 437 ± 25 mm Hg after 120 minutes of perfusion. Throughout the entire EVLP procedure, there was a steady decrease in pulmonary vascular resistance (PVR). Initial PVR was 300 ± 100 dyn×s/cm5; throughout the EVLP, PVR tended to fall, reaching 38,5 ± 12 dyn×s/cm5 at the end of perfusion.Conclusion. A safe and effective EVLP using our perfusate is possible. The developed orthotopic left lung transplantation protocol under circulatory support conditions, supplemented by membrane oxygenation, showed it is efficient and reliable.